Antecedents affecting Intention to Use E-services in Bangladesh Police-: An Application of TAM - Tirno, Rabbir Rashedin (Jahangirnagar University Journal of Management Research, 2024)
Over the last two decades, government e-services have become popular worldwide. This study explores the antecedents affecting the intention of police officers (POs) to use e-services in Bangladesh. The study used survey data from 243 POs working in 26 police stations nationwide using purposive sampling. MS Excel and SmartPLS 4.2 were used to analyze the survey data. The outcome of the analysis indicates that information quality, service quality, and system quality have a direct positive influence on perceived usefulness (PU) of e-services in the Police department. However, these three antecedents do not influence police officers’ perceived ease of use (PEU). However, PEU has a direct positive effect on intention to use (IU) but no effect on PU. The study will assist policymakers in understanding the behavior of police officers in using e-services to serve citizens. It will also allow them to design a system for the e-services that will assist citizens of Bangladesh in a better way in terms of public security.